A heuristic energy-aware approach for hard real-time systems on multi-core platforms - He, Da; Müller, Wolfgang (Microprocessors and Microsystems - Embedded Hardware Design 37(6-7))

Embedded Systems: Design, Analysis and Verification. Proceedings of the 4th IFIP TC10 International Embedded Systems Symposium, IESS 2013, Paderborn, Germany, June 2013

Organic Programming of Real-Time Operating Systems - Khaluf, Lial; Rammig, Franz-Josef (The Ninth International Conference on Autonomic and Autonomous Systems)

Methods for the Design and Development - Anacker, Harald; Dellnitz, Michael; Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Horenkamp, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Korf, Sebastian; Krüger, Martin; Müller, Wolfgang; et al. (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Learning Efficient Information Extraction on Heterogeneous Texts - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the Sixth International Joint Conference on Natural Language Processing)

Information Extraction as a Filtering Task - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the 22nd ACM International Conference on Conference on Information & Knowledge Management)

Automatic Pipeline Construction for Real-Time Annotation - Wachsmuth, Henning; Rose, Mirko; Engels, Gregor (14th International Conference on Intelligent Text Processing and Computational Linguistics)

Practical algorithms for clustering and modeling large data sets - Analysis and improvements - Kuntze, Daniel

An Approach for Determining Optimal Contrast in Visual Cryptography - Juhnke, Jakob; Lefmann, Hanno; Strehl, Volker

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (J. Cryptology)

Practical Signatures from Standard Assumptions - Böhl, Florian; Hofheinz, Dennis; Jager, Tibor; Koch, Jessica; Hong Seo, Jae; Striecks, Christoph (Advances in Cryptology - EUROCRYPT 2013, 32nd Annual International Conference on the Theory and Applications of Cryptographic Techniques, Athens, Greece, May 26-30, 2013. Proceedings)

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

Bounded Model Checking of Graph Transformation Systems via SMT Solving - Isenberg, Tobias; Steenken, Dominik; Wehrheim, Heike (Formal Techniques for Distributed Systems - Joint IFIP WG 6.1 International Conference, {FMOODS/FORTE} 2013, Held as Part of the 8th International Federated Conference on Distributed Computing Techniques, DisCoTec 2013, Florence, Italy, June 3-5, 2013. Proceedings)

SPIN as a Linearizability Checker under Weak Memory Models - Travkin, Oleg; Mütze, Annika; Wehrheim, Heike (Hardware and Software: Verification and Testing - 9th International Haifa Verification Conference, HVC 2013, Haifa, Israel, November 5-7, 2013, Proceedings)

A High-Level Semantics for Program Execution under Total Store Order Memory - Dongol, Brijesh; Travkin, Oleg; Derrick, John; Wehrheim, Heike (Theoretical Aspects of Computing - ICTAC 2013 - 10th International Colloquium, Shanghai, China, September 4-6, 2013. Proceedings)

Temporal Reconfiguration Plans for Self-Adaptive Systems - Ziegert, Steffen; Wehrheim, Heike (Software Engineering 2013: Fachtagung des GI-Fachbereichs Softwaretechnik, 26. Februar - 2. März 2013 in Aachen)

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Approaches for an informational separation of powers in learning platforms - Keil, Reinhard; Winkelnkemper, Felix

„Do You Speak Usability?“ – Aktueller Stand des Glossars und des Curriculums für den „Certified Professional for Usability and User Experience (CPUX)“ der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter; Polkehn, Knut

Contextual tagging in the coactive knowledge organization - K {\ "u} hnel, Birger

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten

Computer science and education - A struggle for creative sovereignty in society? - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix (FIfF-Kommunikation)

Media contexts - context media - Keil, Reinhard

A Taxonomy-Based Approach Towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard

Adapting Hardware Systems by Means of Multi-Objective Evolution - Kaufmann, Paul
Reconfigurable circuit devices have opened up a fundamentally new way of creating adaptable systems. Combined with artificial evolution, reconfigurable circuits allow an elegant adaptation approach to compensating for changes in the distribution of input data, computational resource errors, and variations in resource requirements. Referred to as ``Evolvable Hardware'' (EHW), this paradigm has yielded astonishing results for traditional engineering challenges and has discovered intriguing design principles, which have not yet been seen in conventional engineering. In this thesis, we present new and fundamental work on Evolvable Hardware motivated by the insight that Evolvable Hardware needs to compensate for events with different change rates. To solve the challenge of different adaptation speeds, we propose a unified adaptation approach based on multi-objective evolution, evolving and propagating candidate solutions that are diverse in objectives that may experience radical changes. Focusing on algorithmic aspects, we enable Cartesian Genetic Programming (CGP) model, which we are using to encode Boolean circuits, for multi-objective optimization by introducing a meaningful recombination operator. We improve the scalability of CGP by objectives scaling, periodization of local- and global-search algorithms, and the automatic acquisition and reuse of subfunctions using age- and cone-based techniques. We validate our methods on the applications of adaptation of hardware classifiers to resource changes, recognition of muscular signals for prosthesis control and optimization of processor caches.

Das Verteilungsproblem für mechatronische Systeme - Hüwe, Marcus

Simulationsgestützter Entwurf für Elektrofahrzeuge - Farshizadeh, Emad; Briese, Hermann; Steinmann, David; Stockmann, Lars; Beringer, Steffen; Holler, Dominik; Klobedanz, Kay; Heinzemann, Christian; Peter, Klaus; Leuer, Michael (8. Dortmunder Autotag)
Das Thema Elektromobilität hat in der Fahrzeugindustrie in den letzten Jahren viel Aufmerksamkeit erhalten. Gerade im Bereich der Entwicklung von Steuergeräte-Software ist der Bedarf an frühzeitiger Absicherung hoch. Nur so können Produkteinführungszeiten minimiert und effektiv Entwicklungskosten eingespart werden. Komplexe Werkzeugketten und die verteilte Entwicklung erschweren den Prozess und verlängern die Entwicklungszeit. Das Förderprojekt „Simulationsgestützter Entwurf für Elektrofahrzeuge“, kurz „E-Mobil“, nimmt sich der Herausforderungen einer verteilten Entwicklung von Steuergeräte-Software an. Vier Projektpartner aus Industrie und Forschung untersuchen die Besonderheiten sowohl bzgl. des Entwurfsprozesses, als auch der beteiligten Entwurfswerkzeuge im Vergleich zur konventionellen Fahrzeugentwicklung. Im Fokus stehen die Modellierung und die simulationsgestützte Absicherung in frühen Entwurfsstadien. Die Modellierung umfasst Regelungssoftware sowie die für die Simulation nötigen elektrischen und mechatronischen Komponenten. Die vorliegende Arbeit stellt die Kernthemen sowie aktuelle Ergebnisse aus dem Projekt vor.

Combining Scenario-based and Architecture-based Timing Requirements - Koch, Thorsten
Die in der Automobilindustrie verwendeten eingebetteten Systeme gehören zu den komplexesten eingebetteten Systemen. Die Automobilhersteller sind in der Entwicklung ständig bemüht sowohl die Sicherheit und den Komfort des Fahrers also auch der anderen Insassen zu verbessern. Die meisten der entwickelten Systeme sind sowohl zeit- als auch sicherheitskritisch. Einer Studie von Mercedes-Benz zufolge resultieren 80% der Innovationen in der Automobilbranche aus neuen Elektronikkomponenten, deren Funktionen zu 90% durch Software realisiert wird. Um die steigende Komplexität in der Entwicklung von eingebetteten Systemen zu beherrschen wird in der Automobilbranche immer öfter die modelbasierte Softwareentwicklung anstelle der klassischen Programmierung eingesetzt. Im Requirements Engineering, der ersten Phase der Entwicklung eines Produktes, werden die Anforderungen gesammelt und dokumentiert. Die Dokumentation erfolgt mittels natürlicher Sprache. Modellbasierte Ansätze werden heutzutage höchstens unterstützend eingesetzt. Während des Requirements Engineerings muss der Requirements Engineer sowohl die funktionalen Anforderungen an das zu entwickelnde System als auch seine zeitlichen Anforderungen spezifizieren und analysieren. Die funktionalen Anforderungen umfassen dabei insbesondere die Kommunikation zwischen den verschiedenen Teilsystemen. Szenarien stellen eine intuitive Möglichkeit zur Modellierung von funktionalen Anforderungen dar. Im Rahmen dieser Arbeit wird ein modellbasierter Ansatz zur Modellierung von Szenarien verwendet. Anforderungen an das zeitliche Verhalten werden innerhalb der Architektur spezifiziert. Dazu stehen in der Automobilbranche Architekturbeschreibungssprachen wie EAST-ADL zur Verfügung. Obwohl sowohl funktionale als auch zeitliche Anforderungen an das System spezifiziert und analysiert werden müssen, existiert bisher keine Methodik, die beide Ansätze miteinander kombiniert. Aus diesem Grund wurde im Rahmen dieser Arbeit eine neue Requirements Engineering Methodik entwickelt, die eine systematische und ganzheitliche Spezifikation und Analyse der funktionalen und zeitlichen Anforderungen bereitstellt. Wir haben zwei Modelltransformationen entwickelt, um den Requirements Engineer beim Übergang von den funktionalen zu den zeitlichen Anforderungen zu unterstützen. Die vorliegende Arbeit wird durch eine Evaluierung der Methodik, sowie der Modelltransformationen auf Basis eines Komfortsteuergerätes abgerundet.

Darstellung heterogener 3-D-Szenen in Echtzeit - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)
Viele virtuelle 3-D-Szenen im industriellen Bereich sind nicht gleichmäßig strukturiert, z.B. weil sie eine stark unterschiedliche Dichteverteilung der Polygone aufweisen. Für solch heterogene Daten existiert kein Algorithmus, der die Gesamtheit der Daten sowohl schnell als auch mit guter Qualität darstellen kann. Die Auswahl der richtigen Algorithmen für einzelne Szenenteile durch einen Experten ist zeitintensiv und in vielen Visualisierungssystemen nicht umzusetzen. Um dieses Problem zu lösen, setzt das hier vorgestellte Multi-Algorithmen-Rendering verschiedene Renderingalgorithmen gleichzeitig ein, um eine virtuelle 3-D-Szene darzustellen. Das Verfahren unterteilt die Szene dafür in einem Vorverarbeitungsschritt automatisch in geeignete Teilregionen und bestimmt deren Eigenschaften. Diese Daten werden zur Laufzeit dazu genutzt, um ständig für den aktuellen Standpunkt des Betrachters eine Abschätzung der Qualität und Laufzeit der zur Auswahl stehenden Renderingalgorithmen zu berechnen. Durch die Lösung eines Optimierungsproblems kann so bei vorgegebener Bildrate durch die passende Zuordnung der Algorithmen zu den Regionen die Bildqualität optimiert werden – bei automatischer Anpassung an die Leistungsfähigkeit der eingesetzten Hardware. In einer experimentellen Evaluierung vergleichen wir die Laufzeit und Bildqualität des Verfahrens mit denen verbreiteter Standardrenderingverfahren.

Spherical visibility sampling : preprocessed visibility for occlusion culling in complex 3D scenes - Eikel, Benjamin

Algorithmische Grundlagen für die Selbstorganisation von Roboterschwärmen - Meyer auf der Heide, Friedhelm (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, R.; Nudelman, I.; Polevoy, Gleb (Networking, IEEE/ACM Transactions on)
In this paper, we define and study a new problem, referred to as the Dependent Unsplittable Flow Problem (D-UFP). We present and discuss this problem in the context of large-scale powerful (radar/camera) sensor networks, but we believe it has important applications on the admission of large flows in other networks as well. In order to optimize the selection of flows transmitted to the gateway, D-UFP takes into account possible dependencies between flows. We show that D-UFP is more difficult than NP-hard problems for which no good approximation is known. Then, we address two special cases of this problem: the case where all the sensors have a shared channel and the case where the sensors form a mesh and route to the gateway over a spanning tree.
Keywords: Approximation algorithms; Approximation methods; Bandwidth; Logic gates; Radar; Vectors; Wireless sensor networks; Dependent flow scheduling; sensor networks

Light scattering by randomly irregular dielectric particles larger than the wavelength - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optical Letters)
Keywords: tet_topic_scattering

A framework for enhancing dependability in self-x systems by Artificial Immune Systems - Rammig, Franz; Stahl, Katharina; Vaz, Gavin Francis (IEEE Int. Symp. on Object/component/service-oriented Real-time distributed Computing (ISORC))

FPGA Implementation of a Second-Order Convolutive Blind Signal Separation Algorithm - Kasap, Server; Redif, Soydan (Proc. IEEE Signal Processing and Communications Conf. (SUI))

Novel Field-Programmable Gate Array Architecture for Computing the Eigenvalue Decomposition of Para-Hermitian Polynomial Matrices - Kasap, Server; Redif, Soydan (IEEE Trans. on Very Large Scale Integration (VLSI) Systems)

Competitive throughput in multi-hop wireless networks despite adaptive jamming - W. Richa, Andréa; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing)

Corona: A stabilizing deterministic message-passing skip list - Mohd Nor, Rizal; Nesterenko, Mikhail; Scheideler, Christian (Theor. Comput. Sci.)

An Efficient and Fair MAC Protocol Robust to Reactive Interference - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (IEEE/ACM Trans. Netw.)

Quelltextgenerierung für LEGO Mindstorms-Roboter - Geismann, Johannes (Berichtsband der Informatiktage 2013: Smarte Sichten, smarte Schichten)
Die Komplexität von mechatronischen Systemen wird stetig größer. MechatronicUML (MUML) ist eine Methode zur Entwicklung für Software von mechatronischen Systemen. Im Rahmen einer Bachelorarbeit wurde ein bestehender Quelltextgenerator für MUML-Modelle so erweitert, dass Quelltext für ein Echtzeitbetriebssystem generiert werden kann, welches auf einem LEGO Mindstorms-Roboter installiert ist.

Modulare Leistungsprognose von Kompaktsteuerungen - Frieben, Jens; Heutger, Henning; Meyer, Matthias; Becker, Steffen (9. Paderborner Workshop Entwurf mechatronischer Systeme)

An evaluation testbed for adaptive, topology-aware deployment of elastic applications - Keller, Matthias; Robbert, Christoph; Peuster, Manuel (Proceedings of the ACM SIGCOMM 2013 conference on SIGCOMM)

CROWD: An SDN Approach for DenseNets - Ali-Ahmad, Hassan; Cicconetti, Claudio; de la Oliva, Antonio; Draxler, Martin; Gupta, Rohit; Mancuso, Vincenzo; Roullet, Laurent; Sciancalepore, Vincenzo (2013 Second European Workshop on Software Defined Networks)

A Scalable Redundant TDMA Protocol for High-Density WSNs Inside an Aircraft - Blanckenstein, Johannes; Garcia-Jimenez, Javier; Klaue, Jirka; Karl, Holger (Lecture Notes in Electrical Engineering)

Cliquenbildung in verteilten Systemen - Blumentritt, Fritz

Adding Capacity-Aware Storage Indirection to Homogeneous Distributed Hash Tables - Wette, P.; Graffi, K. (2013 Conference on Networked Systems)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks -- Workshops)

Denser Networks for the Future Internet, the CROWD Approach - de la Oliva, Antonio; Morelli, Arianna; Mancuso, Vincenzo; Draexler, Martin; Hentschel, Tim; Melia, Telemaco; Seite, Pierrick; Cicconetti, Claudio (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering)